2004
DOI: 10.1002/hep.20435
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection in a North American adult hemodialysis patient population

Abstract: Hepatitis B virus (HBV) infections continue to occur in adult hemodialysis units. A possible contributing factor is the presence of occult HBV (serum hepatitis B surface antigen [HBsAg] negative but HBV DNA positive). Two hundred forty-one adult hemodialysis patients were screened for occult HBV. HBV DNA testing was performed by real-time polymerase chain reaction (PCR) with 2 independent primer sets (core promoter and surface). Two (0.8%) of the 241 patients were HBsAg positive. Of the remaining 239 HBsAgnega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
103
2
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 34 publications
12
103
2
5
Order By: Relevance
“…Marked variation was found by comparing these rates with OBI prevalence rates reported in other related national or international studies (23) (24) (35) (36) (37) (38) (39) .This variation may be attributed to differences in the sample size of the study populations, demographics, immunologic status of the studied patients, endemicity of HBV infection, levels of viral DNA in the blood, sampling conditions and the types of diagnostic tool(s) used for diagnosis (40) . This comparison also revealed that the prevalence of OBI in our target HD patients was relatively low, possibly due to the application of safety precautions during the dialysis process in these units and the implementation of the routine vaccination program.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Marked variation was found by comparing these rates with OBI prevalence rates reported in other related national or international studies (23) (24) (35) (36) (37) (38) (39) .This variation may be attributed to differences in the sample size of the study populations, demographics, immunologic status of the studied patients, endemicity of HBV infection, levels of viral DNA in the blood, sampling conditions and the types of diagnostic tool(s) used for diagnosis (40) . This comparison also revealed that the prevalence of OBI in our target HD patients was relatively low, possibly due to the application of safety precautions during the dialysis process in these units and the implementation of the routine vaccination program.…”
Section: Discussionmentioning
confidence: 97%
“…This result is in accordance with the fi nding that OBI is more prevalent in seropositive patients who are positive for anti-HBc and/or anti-HBs (23) (29) (37) (42) (43) . The occurrence of occult infection despite the presence of neutralizing an ti-HBs can result from mutations affecting the S region of the HBV genome (39) . However, the absence of all HBV serological markers (even anti-HBc) in some HBV DNApositive patients strengthens the proposal that the detection of viral DNA is the gold standard for the diagnosis of OBI.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of occult HBV in our hemodialysis patient population is not high compared with that in the general population, it is considerably high compared with other studies. In a study by Minuk et al 16 including 239 hemodialysis patients who were hepatitis B surface antigen-negative, 9 (3.8%) patients were HBV DNA-positive by real-time PCR. In another study by Yakaryilmaz et al 17 of 188 patients with end-stage renal disease on maintenance hemodialysis (mean duration 98 ± 66 months), occult HBV was identified in only five (2.7%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral exposure also favors contamination by HCV (Dai et al, 2001). The studies performed up to now on hemodialysis patients provide widely divergent results, reporting a prevalence of occult HBV that ranges from 0% to 36% (Besisik et al, 2003;Fabrizi et al, 2005;Goral et al, 2006;Kanbay et al, 2006;Minuk et al, 2004;Motta et al, 2010;Siagris et al, 2006). These apparent discrepancies may be explained by significant differences in the prevalence of HBV infection in different geographic regions and/or by the detection limits of different HBV-DNA assays.…”
Section: Occult Hbv Infection In Hemodialysis Patientsmentioning
confidence: 99%
“…These apparent discrepancies may be explained by significant differences in the prevalence of HBV infection in different geographic regions and/or by the detection limits of different HBV-DNA assays. In this context, it is of note that several authors consider occult HBV as a possible source of virus spread in hemodialysis units, thus representing a risk of infection for both patients and staff, and suggest some precautions including HBV DNA screening for all hemodialysis patients (Minuk et al, 2004).…”
Section: Occult Hbv Infection In Hemodialysis Patientsmentioning
confidence: 99%